Revealing the predictability of intrinsic structure in complex networks - Jiachen Sun (Nature Portfolio, 2020)
The likelihood of linking within a complex network is of importance to solve real-world problems, but it is challenging to predict. Sun et al. show that the link predictability limit can be well estimated by measuring the shortest compression length of a network without a need of prediction algorithm.